The incidence of pulmonary embolism and associated FDG-PET findings in IV contrast-enhanced PET/CT - Flavell, Robert R; Behr, Spencer C; Brunsing, Ryan L; Naeger, David M; Pampaloni, Miguel Hernandez (Academic radiology, 2014)
Most fluorine-18 fluorodeoxyglucose (FDG)-positron emission tomography with computed tomography (PET/CT) studies are performed on cancer patients. These patients are at increased risk of pulmonary embolism (PE). In this retrospective review, we determined the rate of PE, and the prevalence of associated FDG-PET findings on intravenous (IV) contrast-enhanced PET/CT. We identified all PET/CT studies performed at our institution with a reported finding of PE between January 2005 and October 2012. The medical record was reviewed for symptoms, which were identified after the diagnosis of PE, and whether the patients received treatment. The prevalence of associated FDG-PET findings was determined. A total of 65 total cases of PE (of 182,72 total PET/CT examinations) were identified of which 59 were previously unknown. This gives an incidental PE (IPE) rate of 0.32%. Of the patients where sufficient clinical information was available, 34 of 36 (94%) were treated either with therapeutic anticoagulation or inferior vena cava filter, and 30 of 36 (83%) were asymptomatic in retrospect. Of the patients with IPE, we found nine (15.2%) with associated focal pulmonary artery hypermetabolism, three (5.1%) with hypermetabolic pulmonary infarction, and one with increased isolated right ventricular FDG uptake (1.7%). One case of chronic PE demonstrated a focal hypometabolic filling defect in a pulmonary artery on PET. We found IPE in 0.32% of PET/CT scans. Focal pulmonary artery hypermetabolism or hypometabolism, and hypermetabolic pulmonary artery infarction with the "rim sign" were uncommonly associated with PE. These findings could raise the possibility of IPE in non-IV contrast-enhanced PET/CT studies.